FROM VENERATION OF REMAINS TO WORSHIP OF THE NATION:SOCIAL CONSTRUCTION OF “HISTORICAL RELIC” NOTION IN ARGENTINA DURING 19TH CENTURY. - Blasco, Maria Elida (Revista de Historia Social y de las Mentalidades, 2021)
This article rebuilds contexts upon which the collective imagination started to associate to the notion of “relic” the objects connected with the Independence heroes, forging, thus, a new use of this concept. As getting back and adapting the Christian worship of venerating “remains” which had come from, or had come in contact with the body or blood of either Christ or the saints. It was in Latin America and Argentina during the 19th century that the vestiges of some political figures started to be considered “historical relics” and therefore subjects to exaltation as they had belonged to “heroes” and “martyrs” of the nation. From that point, it is conjectured that the liberal leadership introduced civic worship of the nation as it juxtaposed historical value with collections of Christian martyrdom, worship to the dead and relic devotion.